Who is enrolled in the Australian BA? Student uptake of the Australian BA 2001-2006. - Gannaway, Deanne; Trent, Faith; Upton, Hayley; Price, Sarah (Australian Learning and Teaching Council, 2008)
Report from a project that aimed: To understand the nature and role of a Bachelor of Arts degree in contemporary Australia; To map the diverse Bachelor of Arts programs on offer in Australia between 2001-2008; To identify the major strengths, difficulties, capabilities and contributions of the program; and to provide rich base-line data on the nature and models of BAs to be accessible for future curriculum planning for arts faculties. This report presents the key findings from the BA scoping project that document the trends in student uptake of programs within the field of Arts offered across Australia.